2016
DOI: 10.1007/s13762-016-1073-5
|View full text |Cite
|
Sign up to set email alerts
|

Bio-treatment and water reuse as feasible treatment approaches for improving wastewater management during flotation of copper ores

Abstract: Established and emerging technologies for treatment of flotation wastewaters are compared and discussed in the context of their applicability during the management of wastewaters from Cu-Co ores processing through flotation in the Katanga province of the Democratic Republic of Congo. The effects from water recycling on water quality and flotation performance are briefly presented in parallel. The ore processing schemes and the wastewater management practices at two operational concentrators are illustrated as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…However, with increasing the current density (that means also the cell voltage) reactions ( 7) and ( 8) can not be excluded. Oxygen formed, together with the oxygen naturally dissolved in water, may further oxidize Fe(II) to Fe(III) to form Fe(OH) 3(S) [44,45]: 4Fe2+ + 10H2O + O2(g) → 4 Fe(OH)3(s) + 8H+ (15) and protons formed can be neutralized with the OH − produced in reaction (2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with increasing the current density (that means also the cell voltage) reactions ( 7) and ( 8) can not be excluded. Oxygen formed, together with the oxygen naturally dissolved in water, may further oxidize Fe(II) to Fe(III) to form Fe(OH) 3(S) [44,45]: 4Fe2+ + 10H2O + O2(g) → 4 Fe(OH)3(s) + 8H+ (15) and protons formed can be neutralized with the OH − produced in reaction (2).…”
Section: Resultsmentioning
confidence: 99%
“…However, returning of only clarified wastewater back to flotation can slowly lead to disturbance in flotation process and deteriorate its results due to increased water salinity, accumulation of heavy metal ions and residual reagents, and increase in the amount of slimes [14,15]. For instance, the recycling of the untreated wastewater back to flotation has led to decrease of lead grade in lead concentrate by 62 %, compared to the concentrate obtained at fresh water using [11].…”
mentioning
confidence: 99%
“…Samples of wastewater from the flotation of Cu and Co oxidized ores carried out at the NCK have an average temperature of 24 °C. They are highly conductive as proven by their higher electric conductivity (3.7 Ms/cm) in relationship with their great saltiness brought by ionic species resulting from the partial dissolution of minerals subjected to flotation together with reagents added to the pulp in view enhancing their recovery (Mbaya 2014(Mbaya , 2015Shengo 2013). The same samples consist of alkaline water (Mbaya 2014(Mbaya , 2015Mwamba 2013;Shengo 2013), loaded with matters in suspension (Mbaya 2015) and of which the dissolved oxygen content is of about 450 mg/L.…”
Section: Nck Wastewater Physicochemical Characteristicsmentioning
confidence: 99%
“…Different researches carried out on waste water from the flotation of minerals at the NCK have focused more on highlighting the environmental pollution that it could cause and solutions have been suggested either to minimise the adverse effects on the environment (Countois et al 2003;Bwapwa 2019) or to recycle the water in the flotation process with the aim of utilizing the unconsumed flotation reagents that are feared to adversely affect aquatic fauna and flora as well as human health (Shengo 2013;Shengo and Mutiti 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to Shengo and Mutiti (2016), Chae (2016), CO2 generated in livestock wastewater treatment could be recycled to a flotation system for sludge thickening. Results also indicated that CO2 recycling didn't create negative impact on methane production potential.…”
Section: Coagulation/flocculationmentioning
confidence: 99%